Paths of tutoring and learning about health and citizenship - Lívia Samila Bezerra Borges; Virgílio Pimentel de Araújo; Rammon Diego Protásio Oliveira; Renan Ribeiro Barborsa Alves; Allyson Carvalho Araújo (Rev Rene)
The new paradigm of the attention to health hasbeen discussed since the decade of the 70´s and fromthe Movement of the Brazilian Sanitation Renovation,the need of transformation of the health professionalwas highlighted among other demands. From theunfolding of such movement the Universidade Federaldo Rio Grande do Norte (UFRN) has contemplated theproposals of change in education since the year 2000and organized areas in health formation turned tothe stimulus of interdisciplinary practices and to thearticulation concerning teaching-service-community.The Atividade Integrada de Educação, Saúde eCidadania (Integrated Activity in Education, Healthand Citizenship) (SACI, in Portuguese), which is acommon curricular syllabus to all the health coursesat the UFRN, is an outstanding feature of such thisaim.